Empowering Rural Economies through BUMDes Initiatives in Indonesia - Indah Munfaati; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative study investigates the economic empowerment efforts through the